Wireless data relaying - Alvarez, Derrick Dave T. (Animo Repository, 2007)
We present an algorithm for routing in a single radio, multi-hop wireless network. We utilize RFID system that has a wireless network which uses stationary nodes, such as readers. In this paper, we present an algorithm that would secure present wireless network problems like RF noise, signal propagation, node interference and traffic flows by using a network redundancy algorithm. Unlike previous studies that examined routing design in detail, we examine how the system’s overall throughput changed with different instances. From our two readers, we gather data by counting the speed of each transmission to each reader. In addition, we consider different placement, different time constraint and different data packet size.